Limb swelling consistent with posttraumatic lymphedema after closed upper and lower extremity fractures: A retrospective cohort study - Felix Reinkemeier; Christoph Wallner; Marius Drysch; Sonja Verena Schmidt; Flemming Puscz; Maxi von Glinski; Thomas Armin Schildhauer; Marcus Lehnhardt; Björn Behr; Johannes Maximilian Wagner (PLoS ONE, 2025)
Introduction Secondary lymphedema is a very common clinical issue with millions of patients suffering from pain, recurrent skin infections, and the constant need for a decongestive therapy. Well- established because of oncologic procedures, secondary lymphedema is also a well-known phenomenon after trauma. However, precise epidemiological data of posttraumatic lymphedema upon severe extremity injuries are rare. Methods In the present study, we analyzed a patient cohort of 223 individuals who suffered closed fractures of the upper and lower extremity between 2016 and 2020. All of them simultaneously had a soft tissue injury, of 2nd and 3rd grade according to Tscherne classification. Typical symptoms of lymphedema were recorded in a retrospective cohort analysis through patient anamnesis and compared with documented clinical examination findings. Previous illnesses and trauma-specific characteristics were determined from patient files. Results Of all patients, 36% showed symptoms of secondary lymphedema and 8,5% reported recurrent skin infections, indicating severe lymphedema. Furthermore, comparing patients with and without lymphedema, additional trauma-associated parameters, such as total number of surgeries, degree of soft tissue damage, localization of the fracture in lower extremity, related to lymphedema progress could be identified. Conclusion According to these data, posttraumatic secondary lymphedema has even in closed fractures, especially of the lower extremity, a highly underestimated clinical prevalence. Further prospective studies are required to validate these findings, identify high-risk groups, and guide early prophylactic and therapeutic interventions.